Anti-periodic solutions for Clifford-valued high-order Hopfield neural networks with state-dependent and leakage delays - Huo, Nina; Li, Bing; Li, Yongkun (Zielona Góra: Uniwersytet Zielonogórski)
A class of Clifford-valued high-order Hopfield neural networks (HHNNs) with state-dependent and leakage delays is considered. First, by using a continuation theorem of coincidence degree theory and the Wirtinger inequality, we obtain the existence of anti-periodic solutions of the networks considered. Then, by using the proof by contradiction, we obtain the global exponential stability of the anti-periodic solutions. Finally, two numerical examples are given to illustrate the feasibility of our results.
Keywords: Clifford-valued high-order Hopfield neural network; anti-periodic solution; coincidence degree; time-varying delays